Diagnóstico para a desindustrialização do Brasil: doença holandesa ou custo Brasil ? - Oliveira, Moisés de Sousa (2014)
Considering that the Brazilian industry lost precociously participation in national aggregate in recent years, this study sought to identify the main causes of this deindustrialization occurred in Brazil. There are two sources for such a process: the first is based on the so-called Dutch disease, which suggests that the appreciation of the real exchange rate, due to increased exports of commodities, could have a negative effect on the industry as a whole; and the second grounded in the idea of cost Brazil, which suggests that the negative effect on the industry would be caused by the strong weight of variables such as taxes and wages. Our proposal is to investigate the effect of these variables on the real post deindustrialization process based on the methodology of Vector Autoregressive - VAR. Our results argue that the cost Brazil is much stronger than the Dutch disease hypothesis to explain the decline in the share of industry in GDP.